Cascade photocaging of diazeniumdiolate: a novel strategy for one and two photon triggered uncaging with real time reporting. Issue 68 (10th August 2017) - Behara, Krishna Kalyani; Rajesh, Y.; Venkatesh, Yarra; Pinninti, Bhaskar Rao; Mandal, Mahitosh; Singh, N. D. Pradeep
Abstract : We report a new strategy, viz. cascade photocaging, for protecting diethylamine diazeniumdiolate ( O 2 -position), a light sensitive molecule. Abstract : We report a new strategy, viz. cascade photocaging, for protecting diethylamine diazeniumdiolate ( O 2 -position), a light sensitive molecule. Upon photolysis, the cascade photocage at first releases the light activatable linker (latent fluorophore) O 2 -caged diazeniumdiolate, which undergoes spontaneous 1, 8-elimination, triggering the release of the diazeniumdiolate anion and the fluorophore.